2003
DOI: 10.1016/j.hep.2003.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors in Liver Development, Differentiation, and Regeneration

Abstract: Transcriptional Activation. The liver performs essential functions in the body by uniquely expressing hepatocyte-specific genes encoding plasma proteins, clotting factors and enzymes involved in detoxification, gluconeogenesis, glycogen synthesis, and glucose, fat, and cholesterol metabolism. 1 Functional analysis of numerous hepatocyte-specific DNA regulatory regions (promoter and enhancer regions) reveals that they are composed of multiple cis-acting DNA sequences that bind different families of liver-enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
200
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(210 citation statements)
references
References 195 publications
(258 reference statements)
5
200
1
4
Order By: Relevance
“…Hepatocyte nuclear factors (HNFs) are a group of phylogenetically unrelated transcription factors that regulate the transcription of a diverse group of genes, including certain genes that are important for hepatic functions, such as morphological and functional differentiation of hepatocytes, glucose transport and metabolism [83]. Among the HNFs, HNF3α/Foxa1, HNF3β/Foxa2, and HNF4α/MODY1 have been shown to play essential roles in hepatic/pancreatic/intestine development [84].…”
Section: Resultsmentioning
confidence: 99%
“…Hepatocyte nuclear factors (HNFs) are a group of phylogenetically unrelated transcription factors that regulate the transcription of a diverse group of genes, including certain genes that are important for hepatic functions, such as morphological and functional differentiation of hepatocytes, glucose transport and metabolism [83]. Among the HNFs, HNF3α/Foxa1, HNF3β/Foxa2, and HNF4α/MODY1 have been shown to play essential roles in hepatic/pancreatic/intestine development [84].…”
Section: Resultsmentioning
confidence: 99%
“…C/EBPa levels are significantly reduced, while those of C/EBPb are upregulated early after the intervention [143,146]. These changes appear to be important for normal hepatic regeneration, as C/Ebpb null mice have defective glucose homeostasis and display impaired liver regeneration [147,148], and C/EBPa may restrain hepatocellular proliferative activity [3]. Nevertheless, cooperative interactions between liver-enriched transcription factors need to occur during regeneration to allow cell proliferation while maintaining liver function.…”
Section: Regulation Of Hepatocellular Quiescence and Proliferationmentioning
confidence: 99%
“…To carry out their complex and varied functions, for which the preservation of their tridimensional organization within the lobule is essential, hepatocytes must express a large complement of enabling genes [3]. Understanding how the pattern of gene expression that defines hepatocellular identity is established has been the subject of intense study for more than two decades, and the principles guiding early hepatic development and differentiation are relatively well known [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Here we reported for the first time that hepatic expression of HNF4α was significantly abundant in fast growing broiler chicken embryos livers than that of slow growing breed. This could be due to the fact that HNF4α play a critical role in liver morphogenesis (Chen et al, 1994;Zaret, 2000;Zaret, 2002) differentiation (Costa et al, 2003) and metabolism (Gonzalez, 2008). Previous studies reported that dexamethasone (Synthetic GCs) mediated up-regulation of human CYP2A6 involves the glucocorticoid receptor and increased binding of HNF4α to the Proximal Promoter (Onica et al, 2008).…”
Section: Discussionmentioning
confidence: 99%